2020
DOI: 10.1096/fj.201902313rr
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of core fucosylation activates cellular signaling dependent on FLT3 expression in a Ba/F3 cell system

Abstract: Fms-like tyrosine kinase 3 (FLT3) is a glycoprotein, that is a member of the class III receptor tyrosine kinase family. Approximately one-third of acute myeloid leukemia (AML) patients have mutations of this gene, and activation of the FLT3 downstream pathway plays an important role in both normal and malignant hematopoiesis.However, the role of N-glycosylation for FLT3 activation remains unclear. In this study, we showed that the N-glycan structures on wild type (WT), internal tandem duplication (ITD), and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 79 publications
(174 reference statements)
0
7
0
Order By: Relevance
“…A cross-linking assay was performed as described previously ( 72 ). Briefly, cells were centrifuged and resuspended in culture medium incubated with or without human recombinant TNFα (5 ng/ml) for 5 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A cross-linking assay was performed as described previously ( 72 ). Briefly, cells were centrifuged and resuspended in culture medium incubated with or without human recombinant TNFα (5 ng/ml) for 5 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that glycosylation is a necessary step for the plasma membrane location of FLT3 [ 21 , 22 ]. Recent studies hint that glycosylation differs in the WT- and ITD-FLT3 proteins [ 29 , 30 ]; however, our results suggest a more complex scenario since SET/FLT3 binding is prior to glycosylation. However, FLT3-SET-RAC1 binding is not sufficient for correct membrane transport because glycosylation inhibition impaired FLT3 membrane transport.…”
Section: Discussionmentioning
confidence: 47%
“…ITD and TKD can induce a robust activation of STAT5. The Ba/F3 cell was an interleukin‐3 (IL‐3)‐dependent cell line and IL‐3 can induce STAT5 phosphorylation in FLT3‐WT Ba/F3 cells 30 . We found that the Golgi entry was essential for mutant‐mediated cellular signaling.…”
Section: Resultsmentioning
confidence: 99%